Performance optimization of transcritical CO2 refrigeration cycle with thermoelectric subcooler - Sarkar J. (My University, 2025)
Use of thermoelectric subcooler is one of the techniques to improve the performance of transcritical CO2 cycle. Thermodynamic analyses and optimizations of transcritical CO2 refrigeration cycle with thermoelectric subcooler are presented in this paper. Further, the effects of various operating parameters on cycle performances are studied. It is possible to optimize current supply, discharge pressure, and CO2 subcooling simultaneously based on maximum cooling COP for thermoelectrically enhanced transcritical CO2 refrigeration cycle to get best performance. Results show that thermoelectric current supply, COP improvement, and discharge pressure reduction increase with increase in cycle temperature lift, with maximum values of 11A, 25.6%, and 15.4%, respectively, for studied ranges. Use of thermoelectric subcooler in CO2 refrigeration system not only improves the cooling COP, also reduces the system high-side pressure, compressor pressure ratio, and compressor discharge temperature, and enhances the volumetric cooling capacity. Component-wise irreversibility distribution shows similar trend with basic CO2 cycle, although values are lower leading to higher second law efficiency. Cooling capacity may be enhanced by increasing the current supply for the same thermoelectric configuration with penalty of COP. Study reveals that thermoelectrically enhanced CO2 refrigeration cycle yields significant performance improvement especially for higher-cycle temperature lift. © 2011 John Wiley & Sons, Ltd.